Comparison study of electromagnetic wave propagation in high and low pressure Ar inductively coupled plasma. (May 2016) - Wei, Xiaolong; Xu, Haojun; Lin, Min; Song, Huimin
Abstract: The electromagnetic wave propagation in plasmas has been investigated based on the hypothetical parameters in a number of previous literature, but the results can't mirror the feature of real plasma sources for waves. In this paper, the two-dimension parameters of Ar inductively coupled plasma (ICP) are investigated under high and low pressure by multi-physics coupling analysis method. Meanwhile, the profiles of electron density are diagnosed by the Langmuir probe for comparison with the simulated. The increasing pressure induces the significant increase of oscillation frequency and collision frequency, while a large density gradient causes the more nonuniform distribution. The wave propagation in ICPs is calculated with Z-transform finite-different time-domain method. The curves of attenuation, transmission and reflection coefficient are obtained versus pressure, frequency and power. The low pressure ICP induces the relative more attenuation of wave in the frequency band (1 GHz–6 GHz), while the high pressure ICP is more effective to the frequency band (6 GHz–17 GHz). The increasing power is conductive to the attenuation within limits. The reflection is complicated due to the high degree of wave vector gradient over a wavelength. Moreover, the pseudo secondary wave source is created inside high electron density region of ICP. Highlights: The Ar-ICP was modeled by multi-physics coupling method in high and low pressure. The parameters distributions of ICP were investigated with the pressure in 2/200 Pa. The wave propagation in ICPs was accurately calculated with ZT-FDTD method. The curves of attenuation, transmission and reflection coefficient were obtained versus pressure, frequency and power. The pseudo secondary wave source was created inside high electron density region of ICP.